1998
DOI: 10.1046/j.1365-2222.1998.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin‐5 messenger RNA expression in a patient with idiopathic hypereosinophilic syndrome

Abstract: Interleukin-5 has a specific role in various eosinophilic activities. It is the predominant cytokine produces by activated T-lymphocytes isolated from patients with idiopathic hypereosinophilic syndrome. We studied a young patient suffering from idiopathic hypereosinophilic syndrome who presented with Horner's syndrome, peripheral neuropathy and skin ulcers. The IL-5 gene expression by CD4+ T-lymphocytes and the peripheral eosinophil count were raised. The skin ulcers continued to deteriorate despite a swift r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These findings suggest a correlation between increased IL‐5 levels and the presence of eosinophilic granules in EM. Our observations corroborate those of other investigators that reported similar granule deposits on muscle fibre surfaces in patients with eosinophilic endomyocardial disease (Tai et al ., 1987) and an increase in IL‐5 mRNA in patients with idiopathic hypereosinophilic syndrome (Ho et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a correlation between increased IL‐5 levels and the presence of eosinophilic granules in EM. Our observations corroborate those of other investigators that reported similar granule deposits on muscle fibre surfaces in patients with eosinophilic endomyocardial disease (Tai et al ., 1987) and an increase in IL‐5 mRNA in patients with idiopathic hypereosinophilic syndrome (Ho et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of concomitant diseases and, consequently, of chronic drug assumption has not been investigated as a possible risk factor for severe liver damage in chronic hepatitis C. In this context a tissue infiltrate of eosinophilic leucocytes has very rarely been described, and its significance is unknown. Conversely an infiltration of eosinophilic leucocytes has been described in various liver diseases, including primary biliary cirrhosis (PBC) [3][4][5][6][7][8][9], primary sclerosing cholangitis (PSC) [10][11][12], idiopathic hypereosinophilic syndrome [13][14][15][16], hepatic allograft rejection [17][18][19][20][21][22][23][24][25][26], graft-vs-host disease [27] and drug-induced liver injuries [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The morphological change of the eosinophils observed in idiopathic hypereosinophilic syndrome (IHS) is variously expressed as ‘immature’, ‘dysplastic’ or ‘activated’. It is reported that in IHS, the plasma level of interleukin (IL)‐5 or the expression of IL‐5 messenger RNA in helper T cells is increased ( Ho et al . 1998 ).…”
Section: Mean Median Standard Deviation ( Sd) and 95% Range (S) Formentioning
confidence: 99%